Human Resource Competence, Budget Transparency, and Internal Control Systems as Determinants of Budget Absorption Effectiveness - Ida Ayu Angge Septiari; Gede Adi Yuniarta; Nyoman Ari Surya Darmawan; I Gusti Made Priyambhada Putra (Jurnal Ilmiah Akuntansi, 2026)
This study examines the relationships between human resource competence, budget transparency, internal control systems, and budget absorption effectiveness in educational institutions. Data were collected through structured questionnaires from 56 financial officers, budget administrators, and internal auditors in public and private secondary and vocational schools. The data were analyzed using multiple linear regression in SPSS 26. The results show that human resource competence, budget transparency, and internal control systems are positively associated with budget absorption effectiveness. Internal control systems have the strongest standardized coefficient, followed by budget transparency and human resource competence. These findings indicate that effective budget execution depends on the combined availability of competent financial personnel, transparent budget information, and reliable internal control mechanisms. The study contributes to public-sector and educational financial management literature by integrating capability, transparency, and control mechanisms into a unified model of budget absorption. The findings also suggest that educational institutions should strengthen financial-management training, improve budget-reporting transparency, and reinforce authorization, monitoring, and risk-assessment procedures.